Autoimmune Disorders of the Nervous System: Pathophysiology, Clinical Features, and Therapy - Bhagavati, Satyakam (Frontiers in Neurology, 2021)
Remarkable discoveries over the last two decades have elucidated the autoimmune basis of several, previously poorly understood, neurological disorders. Autoimmune disorders of the nervous system may affect any part of the nervous system, including the brain and spinal cord (CNS, the central nervous system) and also the peripheral nerves, neuromuscular junction and skeletal muscle (PNS, the peripheral nervous system). This comprehensive overview of this rapidly evolving field presents the factors which may trigger breakdown of self-tolerance and development of autoimmune disease in some individuals. Then the pathophysiological basis and clinical features of autoimmune diseases of the nervous system are outlined, with an emphasis on the features which are important to recognize for accurate clinical diagnosis. Finally the latest therapies for autoimmune CNS and PNS disorders and their mechanisms of action and the most promising research avenues for targeted immunotherapy are discussed.